2020
DOI: 10.1302/2046-3758.91.bjr-2019-0055.r2
|View full text |Cite
|
Sign up to set email alerts
|

Positive transcriptional response on inflammation and joint remodelling influenced by physical exercise in proteoglycan-induced arthritis: An animal study

Abstract: Aims To assess the effect of physical exercise (PE) on the histological and transcriptional characteristics of proteoglycan-induced arthritis (PGIA) in BALB/c mice. Methods Following PGIA, mice were subjected to treadmill PE for ten weeks. The tarsal joints were used for histological and genetic analysis through microarray technology. The genes differentially expressed by PE in the arthritic mice were obtained from the microarray experiments. Bioinformatic analysis in the DAVID, STRING, and Cytoscape bioinform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Also, since stanozolol acts by inducing transforming growth factor 1β synthesis and reducing nitric oxide, it may not significantly impact IL-1 levels. It is also important to keep in mind that exercise influences inflammatory arthropathies parameters, and increase joint loading adds to secondary inflammation in OA joints 48 , 49 . As these animals were working dogs, physical activity may also play a role in this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Also, since stanozolol acts by inducing transforming growth factor 1β synthesis and reducing nitric oxide, it may not significantly impact IL-1 levels. It is also important to keep in mind that exercise influences inflammatory arthropathies parameters, and increase joint loading adds to secondary inflammation in OA joints 48 , 49 . As these animals were working dogs, physical activity may also play a role in this finding.…”
Section: Discussionmentioning
confidence: 99%
“… 35 Although some lines of evidence are conflicted, 36 , 37 systematic inflammatory response and serum LPS are responsive to antibiotic perturbations on gut microbiome. Exercise not only downregulates genes associated with the inflammatory process, 38 but also improves the clearance of endotoxins by Kupffer cells, 39 which indicates that the elimination of systematic inflammatory factors and microbiome-derived metabolites may be the mechanisms of exercise-induced cartilage-subchondral bone unit integrity maintenance. Indeed, our study showed a substantial elimination of LPS and endotoxin in the PTOA exercised animals, whereas PTOA/Sed rats might develop increased gut permeability with endotoxemia in association with upregulation of circulating proinflammatory molecules consistent with an activated innate immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested a link between subchondral bone health and OA. 33 - 35 However, it may be that the softer subchondral bone of the osteoporotic patient flexes proportionately more and is thereby better perfused than the harder sclerotic bone found in OA.…”
Section: Osteoarthritismentioning
confidence: 99%